AI-BASED JOURNALISTIC PRODUCTION IN INDONESIAN ONLINE MEDIA: A STRUCTURAL ANALYSIS WITH A HIERARCHY OF INFLUENCES APPROACH - Maryami; Dinda Dwimanda Wahyuningtias; Hayu Lusianawati (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
This study analyzes how artificial intelligence (AI) adoption transforms news production in Indonesian online media, using the Hierarchy of Influences model by Shoemaker and Reese as the theoretical framework. The research explores how AI does not merely serve as a technical tool but functions as a structural agent influencing media content at the organizational, extramedia, and ideological levels. Using a qualitative-descriptive method based on document analysis, news texts, institutional reports, and regulatory documents from the Indonesian Press Council, the study finds that AI driven automation has reshaped newsroom hierarchies by replacing entry level journalists with algorithmic systems and promoting new roles such as editorial engineers. Additionally, external pressures from platform algorithms, SEO metrics, and audience expectations have significantly shifted editorial logic toward data-driven, market-oriented practices. Ideologically, AI reinforces digital capitalism, privileging speed and virality over journalistic ethics, diversity, and public interest. The study concludes that AI not only changes production techniques but also restructures values within media institutions, highlighting the need for critical regulation, technological literacy, and ethical safeguards in AI-assisted journalism.